Risk factors for operated carpal tunnel syndrome: a multicenter population-based case-control study - Mandes Anna; Lucchini Roberto; Gobba Fabriziomaria; Galli Paolo; Fucksia Serenella; Franceschini Flavia; Fateh-Moghadam Pirous; dell'Omo Marco; Colao Anna; Cancellieri Maria; Broccoli Marco; Ghersi Rinaldo; et al. (BMC, 2009)
Abstract Background Carpal tunnel syndrome (CTS) is a socially and economically relevant disease caused by compression or entrapment of the median nerve within the carpal tunnel. This population-based case-control study aims to investigate occupational/non-occupational risk factors for surgically treated CTS. Methods Cases (n = 220) aged 18-65 years were randomly drawn from 13 administrative databases of citizens who were surgically treated with carpal tunnel release during 2001. Controls (n = 356) were randomly sampled from National Health Service registry records and were frequency matched by age-gender-specific CTS hospitalization rates. Results At multivariate analysis, risk factors were blue-collar/housewife status, BMI ≥ 30 kg/m2, sibling history of CTS and coexistence of trigger finger. Being relatively tall (cut-offs based on tertiles: women ≥165 cm; men ≥175 cm) was associated with lower risk. Blue-collar work was a moderate/strong risk factor in both sexes. Raised risks were apparent for combinations of biomechanical risk factors that included frequent repetitivity and sustained force. Conclusion This study strongly underlines the relevance of biomechanical exposures in both non-industrial and industrial work as risk factors for surgically treated CTS.